A Case Report of Tadalafil-Associated Fixed Drug Eruption. (December 2018) - Chiu, Ada W.; Stenstrom, Robert
Tadalafil is a drug approved for use in erectile dysfunction, but increasingly being used recreationally. There have only been scant case reports on tadalafil causing fixed drug eruption (FDE). Patients who use tadalafil recreationally are less likely to seek medical attention and the diagnosis can often be missed, given the difficulty in diagnosis. However, clinical examination together with a detailed medication history can provide clinicians with good evidence of the association without invasive biopsies. We discuss a 37-year-old male who developed FDE after 2 separate exposures to tadalafil used for recreational purpose. The scar from the first reaction served as a landmark for the second exposure. His lesions resolved 2 days after the initial presentation. The Naranjo adverse drug reaction probability scale (score = 9) indicates a definite adverse drug reaction to tadalafil. We hope to raise awareness of this drug reaction with this case report.